Predictors of treatment outcome among severe acute malnutrition children admitted inpatient therapeutic feeding center in public health facilities of Jigjiga Town, Somali Region, Ethiopia - Mohamed Arab Abdilahi; Shamsedin Mahdi Hassan; Mohamed Omar Osman; Muhumed Haji Abdi (Human Nutrition & Metabolism)
Background: Severe acute malnutrition (SAM) is a major public health problem in Ethiopia, with inconsistent and inconclusive treatment outcomes, particularly in the study area. Objective: Therefore, this study aims to assess the predictors of outcome treatment among SAM under-five children admitted to stabilization centers in public health facilities in Jigjiga Town, Somali Region, Ethiopia, 2021. Methods: A retrospective cohort study at Jigjiga University Sheik Hassen Yabare Comprehensive Specialized Hospital with 418 participants used checklist data entered EPI Data 3.1 and analyzed in SPSS 23, employing Kaplan-Meier and Cox regression to assess variables' association with recovery rate, including significant predictors (p < 0.05) identified through bivariate and multivariate Cox models, and hazard ratios (HR) with 95 % CI. Results: The recovery rate was 62.2 % with a median nutritional recovery time of 13 days. Vitamin A supplementation 1.4(AHR = 1.405 95 % CI: 1.058, 1.865), received plump nut 1.8 (AHR = 1.8, 95 % 1.250, 2.585) pneumonia 0.684 (AHR = 0.684, 95 % CI: 0.508, 0.921), history of diarrhea 0.614(AHR = 0.614, 95 % CI: 0.435, 0.866), correctly filled multi-chart 1.37 1.379 (AHR = 1.379, 95 % CI: 1.060, 1.795) were significantly associated the recovery rate. Conclusion: The study found that the recovery rate remains low compared to the WHO Sphere standard benchmark and similar studies conducted in Ethiopia. To improve the recovery rate, interventions should prioritize ensuring accurate and complete chart documentation by healthcare providers and incorporating nutritional supplements such as Vitamin A.